Antibacterial Activity of Endophyte Fungi from Moringa Leaves (Moringa oleifera) in Gastrointestinal Infection - Seminarwati, Sri; Nuryanti, Siska; Rusli, Rusli (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Moringa leaves (Moringa oleifera) have potential as an antibacterial because they contain tannins, steroids, triterpenoids, flavonoids, saponins, alkaloids, where these compounds can damage bacterial cell membranes. This study aims to determine the isolates of leaf endophytic fungi (Moringa oleifera) which have antibacterial activity against digestive tract infection bacteria using the agar diffusion method. The results of the isolation of the endophytic fungi of Moringa leaves (Moringa oleifera) obtained 6 isolates which were continued with purification and macroscopic examination. The pure isolates obtained were subjected to screening tests on the test bacteria. The isolate with the IFDK-05 code as the most active isolate, were then fermented. The fermented products were then filtered to separate the supernatant and mycelia. This supernatant was then tested for antibacterial activity using agar diffusion. The results of testing the antibacterial activity of moringa leaf endophytic fungi isolate using the diffusion method in order to obtain the diameter of the inhibition zone for Escherichia coli bacteria (9,01 mm), Salmonella thypi (10,70 mm), Shigella disentryae (9,13 mm), and Vibrio cholerae (-10,95mm). Based on the results of this study, isolates of endophytic fungi of Moringa leaves (Moringa oleifera) have antibacterial activity